Government Protection of Human Rights Humans in Indonesia in the Perspective of Maqasid Al-Syari'ah - Zailani Zailani; Zaitun Zaitun; Aslati Aslati (UM Purwokerto Press, 2023)
Research this discuss about protection government to right human rights in Indonesia in the perspective of Maqasid Syari'ah. Problems in guaranteeing right basic man on every individual is Thing which sensitive. Because every decision given will give birth to various perceptions, including what happened in Indonesia. There is often overlap in the implementation of human rights protection. Then the policy that was initiated by government Indonesia should notice rule and elements from five aspect maqasid al-Shari'ah . So study this study view para expert law and para cleric fiqiyah in review government protection regulations for human rights in Indonesia in the perspective of Maqasid al-Shari'ah. This research is literature research and the approach used in this research is a legal approach based on Maqasid al-Shari'ah. The data related to this study were collected through a literature study and presented with technical content analysis, with reference to the arguments and laws and regulations. as data primary and books literature which related as secondary data. The results of this study are that government regulations on right basic man in Indonesia in perspective maqasid al-Shari'ah has been mentioned contextually, although the limitations and details are not complete as in shari'ah Islam. Thing the appear consequence differences in the aspect of determining the size of violence, sanctions and penalties, as well as the impact on the economy and social conditions. However, the formulation and details of human rights regulations in Indonesia still contain values and principles that are in line with Maqasid al-Shari'ah.